Does Investment Climate Matter for Firm Performance? Evidence from Kenyan Manufacturing Firms - Cyprian Amutabi (European Scientific Journal, ESJ, 2023)
The productivity of Kenyan manufacturing firms is way lower than that of many developed economies and has generally exhibited a consistent decline over the last decade. While this productivity trend has largely been attributed to the presence of a high distortionary institutional and business regulatory environment, existing studies on the role of the investment climate in determining firm performance are ostensibly scanty. This study, thus, employed the World Bank panel enterprise data for the period 2007-2013- 2018 in assessing whether investment climate mattered for firm performance in Kenyan manufacturing firms. More particularly, the study sought to establish the role of the court system and property rights ownership in determining firm performance; a feat that remains unexplored in the Kenyan context. The random effects model was estimated while controlling for the year, industry, and firm-specific control variables. The findings revealed that while court inefficiencies significantly impeded labor productivity, property rights ownership significantly increased productivity. Further, human capital positively determines labor productivity. Concerning governance and institutional factors, ISO-certified firms were found to be significantly more productive. Conversely, business licenses and permits constrain firm productivity. Therefore, to ensure unrelenting firm productivity, speedy and just delivery of court rulings on firm-related matters is critical. Secondly, the acquisition of patents relating to product or process innovation by firms enhances product competitiveness. Thirdly, manufacturing firms should invest more in human capital. Finally, the imposition of favorable business licenses and permits by the governments globally coupled with the ISO Certification requirement by firms is integral in optimizing labor productivity.